The Reconstruction of Braemar and Corgarff Castles, 1746 - Bulloch, John Malcolm (Proceedings of the Society of Antiquaries of Scotland, 1931)
Details of the cost of reconstruction have been taken from the Ordnance Expense Ledger and presented in chronological order.